PENGARUH KUALITAS PRODUK, DAN HARGA TERHADAP NIAT BELI ULANG DENGAN KEPUASAN SEBAGAI VARIABEL INTERVENING (Studi Pada Pelanggan Jilbab Rabbani) - JUWITA KARTIKA DEWI, SISCA; LESTARI ANDJARWATI, ANIK (Jurnal Ilmu Manajemen (JIM), 2018)
Abstract The development of Muslim fashion lately in Indonesia increasingly heard. With the development of Muslim fashion in Indonesia is also developing jilbab brands in Indonesia. Many brands also brand veils or hijab that exist in Indonesia. One of the famous hijab brnd in Indonesia is Rabbani. The purpose of this study is to analyze and discuss the effect of product quality, and price on the intention to buy back through the satisfaction as a variable intervening. Satisfaction is measured by some drivers of satisfaction to determine how much the level of repurchase intention made by Rabbanis hijab customers. The sampling method is nonprobability sampling and the sampling technique is using judgemental sampling with a sample of 220 respondents. The population in this study is the customer of Jilbab Rabbani who is at least 18 years old who had bought or used the headscarf Rabbani. The measuring instrument used is a questionnaire. Analyzer uses path analysis with AMOS 24 program. The results of this study indicate that product quality, and price have a significant effect on satisfaction. The quality of the product has a significant effect on the buy-back intention, while the price has no effect on the buy-back intention. The results of this study also show that product quality, and price have an indirect effect on the intention of buy back and through satisfaction as intervening variable. But the first mediation test (product quality) is proven partially while the price is fully proven. Keywords: product quality, price, customer satisfaction, re-purchase intention